A Study on Influential User Identification in Online Social Networks. Issue 3 (1st May 2016) - Wang, Nan; Sun, Qindong; Zhou, Yadong; Shen, Si
Abstract : Influential user evaluation is great importance in many application areas of online social networks. In order to identify influential users in a more adequate and practical way, we propose a Dynamic regional interaction model (DRI) to evaluate user influence in online social networks. Influential users can be identified by the influence effect on different distance users based on dynamic regional interaction model. We have applied the influential user identification method to Sina Weibo and the experimental results show that compared with the existing methods the proposed method can identify the influence users in a more accuracy and efficiency way.